Molecular variability of watermelon mosaic virus isolates from Argentina - Pozzi, Elizabeth Alicia; Perotto, Maria Cecilia; Bertin, S.; Manglli, A.; Luciani, Cecilia Elizabeth; Conci, Vilma Cecilia; Tomassoli, L. (Springer, 2020)
Watermelon mosaic virus (WMV) is an economically important virus of cucurbit crops in Argentina. The available information on genetic variability must be continuously updated. In this study, we assessed the molecular variability of WMV isolates in Argentina based on the partial sequences of the NIb-CP region and compared them with isolates previously reported from around the world. Forty-six WMV isolates were obtained from naturally infected cucurbit crops collected from 10 provinces between 2011 and 2018. At the molecular level, WMV isolates were grouped into three distinct major phylogenetic groups based on genetic distance. Majority of the Argentine isolates belonged to the emerging group (G3), whereas one isolate was included in G1 and another cluster in G2. G3 was further divided into 5 subgroups, named EM1, EM2, EM3, EM4, and a new group “EMArg”, composed exclusively of Argentine isolates with high bootstrap support and high level of significance. Tajima’s D and Fu were significantly negative for G3 and EMArg, indicating that the population of this subgroup has recently expanded. AMOVA analysis showed that the isolates was not well correlated with their geographic origin. The fixation index (FST) value between the WMV isolates from the different provinces in Argentina was lower than 0.33, indicating a relatively frequent gene flow between provinces. In every group, the predominant evolutionary pressure was negative with a mean dN/dS < 1, suggesting a slow replacement fixation rate. One recombination event was detected involving isolates of EM2 cluster from Argentina.